Effect of plateletpheresis on donor variables and platelet yield using three different cell separators: Experience from tertiary care hospital - Sarita Sharma; Sunita Bundas; Nippun Prinja; Amit Sharma; Rachna Narain (Asian Journal of Transfusion Science)
INTRODUCTION: Platelet collection by apheresis is common nowadays. Many cell separators are available in the market for the same. This study was conducted to study the effect of various donor factors on platelet yield and the effect of different cell separator variables on platelet yield. MATERIALS AND METHODS: This cross-sectional study was done on 600 healthy apheresis platelet donors from April 2016 to March 2017 using three different cell separators. Donor variables, pre, and post-plateletpheresis hematological parameters, machine variables, platelet yield were observed. RESULTS: Postprocedural decline in hematological variables was seen. A positive correlation was seen with pre-apheresis platelet count, blood volume processed, and product volume. Product volume obtained was highest with COM. TEC. Mean platelet yield was maximally seen in Amicus. CONCLUSION: Main predictors of platelet yield are platelet count and volume processed. Donors with lower hemoglobin had better yields. Higher platelet counts lead to better product hence platelet increment in the patient.